State-owned enterprises around the world as hybrid organizations - Bruton, G.; Peng, Mike; Ahlstrom, D.; Stan, C.; Xu, K. (2015)
State-owned enterprises represent approximately 10% of global gross domestic product. Yet they remain relatively underexplored by management scholars. Firms have often been viewed dichotomously as either state owned or privately owned. Today, however, we encourage a more nuanced view of state-owned enterprises as hybrid organizations, in which the levels of ownership and control by the state can vary. Drawing on 36 cases from four industries in 23 countries, we lay the groundwork for a richer understanding of state-owned enterprises by management scholars in the future.